Evaluation of Green Material Selection at PGSD Laboratory Building Universitas Samudra - Lestari, Hilda; Mutia, Eka; Lisa, Nova Purnama (Jurnal Teknik Sipil dan Perencanaan, 2023)
In today's modern era, infrastructure development should take into account environmental considerations, such as the use of green materials and eco-labeling. This approach is vital for ensuring the long-term well-being of humanity and preventing further increases in global warming caused by construction practices that disregard safe and environmentally friendly materials. This study is focused on evaluating the selection of green materials in the PGSD Laboratory at Universitas Samudra. The assessment is based on the standards set by the Green Building Council Indonesia (GBCI) for Material Sources and Cycles. Data collection involved interviews with the technical team responsible for construction, on-site observations to assess material usage, and a review of various building documentation files. The interviews revealed that the PGSD Laboratory at Universitas Samudra was designed with a 'green campus' or 'green building' concept, emphasizing the use of environmentally friendly materials. Analysis of the materials used in both the structural and architectural aspects of the PGSD Laboratory found that it met 8 out of 10 green building requirements, achieving an overall percentage of 80% in accordance with the Material Sources and Cycle assessment for Greenship GBCI. The use of such materials has had a positive impact, contributing to energy conservation, the preservation of natural resources, environmental health, user comfort, and waste reduction.